Income Inequality Does Inflation Matter? - Bulir, Ales (IMF Working Papers, 1998)
This paper contributes to the income inequality literature that is based on the traditional Kuznets model. Price stability, financial deepening, level of development, state employment, and fiscal redistribution are found to enhance income equality in a given country. While the effect of price stability is uniform for all levels of GDP per capita, the effect of financial deepening is found to increase with the level of development. Moreover, tight monetary policies do not seem to have any austere effects; low inflation reinforces, rather than counteracts, the income-equalizing effect of fiscal redistribution